2014
DOI: 10.7205/milmed-d-13-00501
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Psychological Distress and Post-Traumatic Stress Disorder in United States Air Force “Drone” Operators

Abstract: The goal of this study is to repeat a survey administered in 2010 to assess for changes in mental health among United States Air Force aircrew operating Predator/Reaper remotely piloted aircraft, also commonly referred to as "drones." Participants were assessed for self-reported sources of occupational stress, levels of clinical distress using the Outcome Questionnaire-45.2, and symptoms of post-traumatic stress disorder (PTSD) using the PTSD Checklist-Military Version. A total of 1,094 aircrew responded to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 20 publications
(11 reference statements)
0
25
0
2
Order By: Relevance
“…Within a spectrum of leadershipevoking contexts, several attributes may be assumed to characterize necessary qualities for successful performance: these include inner drive, tolerance to stress and enterprise ("get-up-and-go") all of which provide an indication of the leader's resourcefulness. Low-level scoring on any of these three attributes is expected to induce negative influences upon subordinates whereas the opposite outcomes may be predicted by high-level scoring [8]. Low levels of stress tolerance imply a greater focus upon oneself to the exclusion of colleagues and subordinates [9] thereby invoking a deterioration of leadership capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Within a spectrum of leadershipevoking contexts, several attributes may be assumed to characterize necessary qualities for successful performance: these include inner drive, tolerance to stress and enterprise ("get-up-and-go") all of which provide an indication of the leader's resourcefulness. Low-level scoring on any of these three attributes is expected to induce negative influences upon subordinates whereas the opposite outcomes may be predicted by high-level scoring [8]. Low levels of stress tolerance imply a greater focus upon oneself to the exclusion of colleagues and subordinates [9] thereby invoking a deterioration of leadership capacity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the GAO report mentioned above reported on several sources of stress and dissatisfaction within the community as part of its review. Other researchers have also measured stress and burnout (Ouma et al, 2011;Chappelle et al, 2014), shift work fatigue (Tvaryanas et al, 2008;Tvaryanas and MacPherson, 2009), and mental health and posttraumatic stress disorder (Otto and Webber, 2013;Chappelle et al, 2012 and within the RPA community. Lastly, in response to concerns about manning, AFMA explored manning requirements within the RPA force.…”
Section: Research Approachmentioning
confidence: 99%
“…Nevertheless, it is not as simple as that. Researchers in the US Defense Department have reported that RPA aircrew 22 face problems such as depression, anxiety, and PTSD at the same rate as pilots that are flying manned aircraft in combat experience (Dao 2013; for more thorough psychological studies see Chappelle et al 2012Chappelle et al , 2013Chappelle et al , 2014bChristen et al 2014;Fitzsimmons & Sangha 2013). Therefore, even if the aircrews of these machines are not in danger of physical harm, they are still very much in danger of suffering psychological and moral harm.…”
Section: Moral Harm Caused By Autonomous Weapons Systemsmentioning
confidence: 99%